Medico-legal documentation of rape or sexual assault: are community-service doctors equipped for the task? - Lamaine Fouche; Johan Bezuidenhout; Chantelle Liebenberg; Anthonio Oladele Adefuye (South African Family Practice)
Background: Following upon two-year internship, community-service doctors make mistakes when they deal with evidence of medico-legal examinations in various settings. These mistakes result in alleged perpetrators being released by courts. This study investigated undergraduate clinical forensic medicine training, based on experiences and opinions of community-service doctors. This article focuses on incidents of alleged rape cases only.